Comparative Study of Topological Indices for Capped and Uncapped Carbon Nanotubes. (9th August 2022) - Nadeem, Muhammad Faisal; Azeem, Muhammad; Farman, Iqra
Abstract: Due to the recent economic crisis of the world, producing low-cost objects in every field of science and engineering is the main topic of research. Making small in-sized objects, low in budget and weight, and efficient in quality is necessary for the present and future world. In this whole scenario, nanotechnology contributing more than enough. Nanomaterials and nano-objects are highly preferable, carbon nanotubes are one of the highly chosen structures of nanomaterials, which is used in different chemical, biological, and technological fields. This thought leads us to study its different aspects of physical and chemical properties. Topological descriptors are used to characterize different molecular structures by making its numerical quantitative analysis. This article deals with different carbon nanotube structures, studying their chemical and physical characterizations and comparing armchair, semicapped, and capped carbon nanotubes. It provides the best option by making comparative analysis with different tools and algorithms.